Advances in patents related to intrapocket technology for the management of periodontitis - Yadav S.K.; Khan G.; Mishra B. (My University, 2025)
Increased prevalence of oral diseases such as gingivitis, periodontitis and dental caries has become major health issue worldwide. Such growing incidence of periodontitis has directly affected the development of drug delivery systems and growth of the market. Since the infections are limited to periodontal pockets or oral cavity, localized intrapocket drug delivery will be more beneficial than conventional systemic administration. Advances in intrapocket technology and innovations in the field of periodontal drug delivery led to increased patent applications. Newer trends like use of mucoadhesive polymers, in situ forming gels, viscosity modifiers, plasticizers etc which can enhance intrapocket retention of drugs have gained considerable attention among researchers and industrialists. Current market is flooded with products such as Periostat, Periochip®, Atridox®, Arestin®, Actisite®, Dentomycin®, and Elyzol® and generics such as metronidazole, levofloxacin, tetracycline, doxycyline and minocycline for intrapocket delivery. There is a need of novel drugs and delivery systems with better efficacy profiles than the existing compounds. Inclusion of novel technologies like films, fibers, in situ forming implants, microparticles, nanoparticles, and liposomes as intrapocket drug delivery has great potential. Development of antibiotic free drug delivery such as antiseptics, host modulators, biofilms inhibitors and antibodies has promising role in the improvement of pathogenesis of periodontitis. Further, this review deals with various innovations in drug delivery and patents related to localized intrapocket administration of medicaments in the implications of periodontitis. © 2015, Bentham Science Publishers.